بعض تطبيقات الأغار المستخلص من الطحلب البحري السوري Pterocladia capillacea - ميهوب حامد; عباس آصف; محمود علي (Latakia University Journal -Biological Sciences Series, 2018)
The aim of this research was to use the agar extracted from the marine Syrian alga Pterocladia capillacea in some applications in microbiology laboratories and some food applications (with ice cream and sweets). The effect of agar concentration on the gel strength was also studied. Increased concentration leads to increased gel strength. The results recorded in this study showed that the agar produced from the Pterocladia capillacea is of high quality and can be used in many applications. This alga can be an important source of future agar production. كان الهدف من هذا البحث هو استخدام الأغار المستخلص من الطحلب البحري capillacea Pterocladia في بعض التطبيقات العملية كتركيب الأوساط الزرعية لاستنبات الجراثيم والفطريات في مخابر الأحياء الدقيقة و كعامل مهلم في بعض الصناعات الغذائية (الآيس كريم والحلويات). دُرس تأثير تركيز الأغار في قوة تهلمه حيث بينت النتائج أنه كلما زاد التركيز ارتفعت قوة التهلم. أثبتت النتائج المسجلة في هذا البحث أن الأغار المنتج من الطحلب Pterocladia capillacea يتمتع بجودة عالية وتسمح خصائصه باستخدامه لأغراض متعددة, ويمكن لهذا الطحلب أن يشكل مصدرا هاما لإنتاج الأغار في المستقبل.